Geometric tolerance and manufacturing assemblability estimation of metal additive manufacturing (AM) processes. (September 2020) - Rupal, Baltej Singh; Anwer, Nabil; Secanell, Marc; Qureshi, Ahmed Jawad
Abstract: Metal additive manufacturing (AM) has become a predominant process for manufacturing complex metal parts. However, research on controlling the geometric tolerances of the metal AM printed parts and assemblies is scarce. This paper presents a methodology to conduct a geometric tolerance and manufacturing assemblability study of the parts manufactured by metal AM. An assembly benchmark test artifact (ABTA) is designed to include mating features with given assembly conditions based on geometric tolerancing quantifiers. For virtual analysis, prediction phase ABTA samples are generated by using systematic and random field theory deviations. The prediction phase deviations are then calibrated using deviations from a numerical simulation based on thermo-mechanical finite element model of the part. These samples or 'skin model shapes' are subjected to geometric tolerance and assemblability study. For experimental validation of the method, geometric tolerance quantification and actual assembly was conducted on laser powder bed fusion (LPBF) fabricated parts. The comparative analysis of the experimental and virtual results validates the new methodology and its ability to provide reliable information regarding assemblability, size dimensions and geometric tolerances. The method can be extended to any AM process for performing a virtual tolerance and manufacturing assemblability study. Graphical abstract: Unlabelled Image Highlights: Benchmark designed with mating components to conduct experimental geometric tolerance and manufacturing assemblability study. A hybrid approach presented for geometric tolerance estimation of the benchmark using random field theory and thermo-mechanical simulations. The method is used to extract standardized geometric dimensioning and tolerancing (GD&T) quantifiers. The method is validated with experimental GD&T characteristics and manufacturing assemblability.